2019
DOI: 10.1292/jvms.18-0479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sevoflurane anesthesia on neuromuscular blockade produced by rocuronium infusion in dogs

Abstract: This study evaluated the effect of sevoflurane anesthesia on neuromuscular blockade with rocuronium in dogs. Six healthy beagle dogs were anesthetized four times with a minimum 14-day washout period. On each occasion, the dogs were administered 1.25-, 1.5-, 1.75-, or 2.0-fold of the individualized minimum alveolar concentration (MAC) of sevoflurane and received an infusion of rocuronium (0.5 mg/kg followed by 0.2 mg/kg/hr) for 120 min. Neuromuscular function was monitored with acceleromyography and train-of-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Kumar (2017) conducted a study of NMBAs namely Atracurium and Vecuronium in dogs and found a similar inhalant-sparing effect of the neuromuscular blocking agent. In addition to this neuromuscular blockade produced by neuromuscular blocking agents could be potentiated by inhalant anaesthetic agents (Nagahama et al 2006, Sakata et al 2019, further, substantiating the fact that neuromuscular blocking agents had an inhalant sparing effect.…”
Section: Resultsmentioning
confidence: 77%
“…Kumar (2017) conducted a study of NMBAs namely Atracurium and Vecuronium in dogs and found a similar inhalant-sparing effect of the neuromuscular blocking agent. In addition to this neuromuscular blockade produced by neuromuscular blocking agents could be potentiated by inhalant anaesthetic agents (Nagahama et al 2006, Sakata et al 2019, further, substantiating the fact that neuromuscular blocking agents had an inhalant sparing effect.…”
Section: Resultsmentioning
confidence: 77%